PENERAPAN MODEL PEMBELAJARAN PROBLEM SOLVING DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SD KRISTEN PATTI - Kapiluka, Marthen F. O.; Sairiltiata, Sefanya; Septory, Jekriel (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study is to improve student learning outcomes by applying the Problem-Solving Learning Model in Social Studies in fourth-grade students at Patti Christian Elementary School. The research method used in this study is a qualitative approach with Classroom Action Research (CAR). Data collection methods used in this classroom action research include tests, observation, and documentation. The results of the initial test on fourth-grade students at Patti Christian Elementary School showed an average score of 45.62, an increase in cycle I after the teacher implemented the problem-solving learning model, with an average score of 67. The average score in cycle II was 80.92. Student learning outcomes improved in the final test of cycle II. In addition to student learning outcomes, observation and interview results also showed that students were generally very interested in applying the problem-solving learning model to natural resources.